An outbreak ofShigella boydiiserotype 20 in January 2015 amongst United Kingdom healthcare workers involved in the Ebola response in Sierra Leone. Issue 11 (November 2018) - Todkill, Daniel; Pudney, Rachel; Terrell, Andrew; Tuck, Jerry; Hutley, Emma; Dallman, Timothy J.; Jenkins, Claire; Manuel, Rohini; Wade, Michael; Puleston, Richard; Hawker, Jeremy
Abstract : N/A: In January 2015, Public Health England and the United Kingdom (UK) Ministry of Defence investigated cases of diarrhoea and fever in military personnel recently returned to the UK after supporting the response to the Ebola epidemic in Sierra Leone. Tests for Ebola virus infection were negative. PCR tests detected the ipaH gene in 10/12 faecal specimens, and Shigella boydii serotype 20 was isolated from 7 patients. A case control study was undertaken and analysed using multivariable logistic regression. Consumption of a coronation chicken lunch at the transit camp in Sierra Leone (SL) 24‐48 h prior to departure for the UK was significantly associated with disease [adjusted odds ratio (OR) 28.15, 95 % CI: 1.87‐422.65]. In the context of heightened concern during the Ebola epidemic, this outbreak highlights the importance of rapid and effective microbiological and epidemiological investigations to identify the aetiological agent in patients presenting with fever and diarrhoea.